EVALUASI PROGRAM KAMPUNG KELUARGA BERKUALITAS (KB) DI DESA TAMBAK KALISOGO KECAMATAN JABON KABUPATEN SIDOARJO - Naila Trisna Sa'adah; Hendra Sukmana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This research aims to analyze the evaluation of the Family Planning Village program in Tambak Kalisogo Village and the impacts resulting from these activities. The research method is qualitative based through observation, interviews and documentation. Informants were determined using purposive sampling, which included family planning instructors from Jabon sub-district, the PKK chairman of Tambak Kalisogo Village, and the local community. The research focus refers to Edward A. Suchman's evaluation theory which consists of six indicators. 1) the aim of the program is to create a prosperous and independent society. However, the Family Planning Village program in Tambak Kalisogo Village needs to clarify and improve the evaluation mechanism. 2) problem analysis, which according to Edward's theory involves systematic stages, shows that in this village there are still obstacles that affect the program, such as limited signals that interfere with communication between the community and family planning cadres. 3) description and standardization of activities is an important element in evaluation, ensuring that the activities carried out comply with the provisions. 4) measurement of change is generally based on program impact, and in this village it is quite in line with existing measurements. 5), the result of this activity is increased public awareness about reproductive health and the importance of getting married at a mature age for teenagers. 6) the impact of the Family Planning Village program in Tambak Kalisogo Village received a positive response from the district in its village development efforts. However, there are still obstacles, such as the large area that only relies on word of mouth information, which can cause communication errors, as well as the low level of community education which affects village growth.